Sodium oligomannate combined with rivastigmine may improve cerebral blood flow and cognitive impairment following CAR-T cell therapy: A case report - Wang, Yan-Li; Zhang, Yuan; Xu, Jun (Frontiers in Oncology, 2022)
Chimeric antigen receptor-T (CAR-T) cell therapy is a breakthrough for B-cell hematological malignancies but is commonly associated with cytokine release syndrome and neurotoxicity and is occasionally complicated by neurological symptoms, such as cognitive disturbances. Currently, no effective treatments for CAR-T therapy-related cognitive impairment are available. Here, we present a 22-year-old patient with cognitive impairment who was treated with CAR-T cells as a salvage therapy for Burkitt lymphoma. One month after CAR-T cell infusion, he experienced memory loss that mainly manifested as forgetting recent-onset events. Two months of rehabilitation and hyperbaric oxygen therapy failed to provide clinical improvement. Subsequently, the patient improved with oral oxiracetam for 5 months. However, after 10 months of withdrawal, he showed significantly worse memory decline. Then, he began to take sodium oligomannate (February 22, 2021). Follow-up testing at 6 months and 12 months revealed maintenance of memory gains with sodium oligomannate alone or in combination with rivastigmine. Our case shows that CAR-T therapy may compromise cognitive function and that sodium oligomannate may have partial efficacy in restoring cognitive performance and activities of daily living. This may provide insights for further applications of sodium oligomannate for neurological symptoms, especially cognitive deficits following CAR-T cell therapy.